2017
DOI: 10.3171/2017.2.spine161310
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic use of intraoperative vancomycin powder and postoperative infection: an analysis of microbiological patterns in 1200 consecutive surgical cases

Abstract: OBJECTIVEWound infections following spinal surgery for deformity place a high toll on patients, providers, and the health care system. The prophylactic application of intraoperative vancomycin powder has been shown to lower the infection risk after thoracolumbar decompression and fusion for deformity correction. The purpose of this study was to assess the microbiological patterns of postoperative surgical site infections (SSIs) after prophylactic use of vancomycin pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 44 publications
2
37
0
1
Order By: Relevance
“…However, the study demonstrated that over half of the patients treated with vancomycin powder who developed SSI were positive for gram-negative pathogens. 2 In a study of 5909 cases of posterior thoracic or lumbar surgeries, Grabel et al found 115 cases of SSI. 12 After a review of the 115 cases of SSI, they found that 42 patients received vancomycin powder while 73 did not.…”
Section: Ssi Secondary To Gram-negative Pathogenmentioning
confidence: 99%
“…However, the study demonstrated that over half of the patients treated with vancomycin powder who developed SSI were positive for gram-negative pathogens. 2 In a study of 5909 cases of posterior thoracic or lumbar surgeries, Grabel et al found 115 cases of SSI. 12 After a review of the 115 cases of SSI, they found that 42 patients received vancomycin powder while 73 did not.…”
Section: Ssi Secondary To Gram-negative Pathogenmentioning
confidence: 99%
“…2 The rates of infection with different organisms following spine surgery vary by study; however, some of the most frequent organisms identified are grampositive cocci including methicillin-resistant Staphylococcus aureus (MRSA) and Staphylococcus epidermidis. 3 Increasing methicillin resistance has decreased the efficacy of intravenous cephalosporins as the standard preoperative antibiotic prophylaxis used in orthopedic procedures in general, and spine surgery in particular. [3][4][5] Studies have reported that more than 60% of wound infection isolates in the United States are cephalosporin-resistant, including MRSA and coagulase-negative Staphylococcus.…”
Section: Introductionmentioning
confidence: 99%
“…3 Increasing methicillin resistance has decreased the efficacy of intravenous cephalosporins as the standard preoperative antibiotic prophylaxis used in orthopedic procedures in general, and spine surgery in particular. [3][4][5] Studies have reported that more than 60% of wound infection isolates in the United States are cephalosporin-resistant, including MRSA and coagulase-negative Staphylococcus. 6,7 Among orthopedic patients in the United States, 20% to 30% have anterior nares colonized by methicillin-sensitive S aureus (MSSA), and 2% to 6% are colonized by MRSA.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus is a leading cause of infection-related morbidity and mortality [1][2][3][4] and the most common cause of postoperative infection. [5][6][7] Erythromycin, penicillin, gentamicin, and vancomycin are typically used for the treatment of S. aureus infection. However, due to the abuse of antibiotics, new multidrug-resistant strains have emerged, thus hindering the management of S. aureus.…”
Section: Introductionmentioning
confidence: 99%